A Double-Edged Sword: The Effects of Stressors on Job Crafting and Career Sustainability - Xintian Li; Hainan Liu; Peng Peng (SAGE Open)
Prior studies have investigated the relationship between work stressors and career sustainability. However, there is currently a lack of information on this relationship’s underlying mechanisms and boundaries. Delving into the complexities of work stressors and their influence on career sustainability, this research employs the job demands-resources model to examine the intricate relationship. This study used hierarchical regression analysis and PROCESS macro for SPSS to explore the mediating role of job crafting and the moderating role of perceived organizational support based on 358 employees from 28 hotel companies in China. The results show that challenge stressors can enhance career sustainability, while hindrance stressors diminish it. Job crafting has a significant mediating effect between work stressors and career sustainability. In addition, perceived organizational support significantly moderates the relationship between work stressors and job crafting. This study significantly advances the literature on job crafting and career sustainability, highlights the complex impact of work stressors in the hospitality industry, and provides actionable insights for workplace stress management initiatives and employee career sustainability promotion.